Solvent-induced on/off switching of intramolecular electron transfer in a cyanide-bridged trigonal bipyramidal complex - Wei, Rong Jia; Nakahara, Ryohei; Cameron, Jamie M.; Newton, Graham; Shiga, Takuya; Sagayama, Hajime; Kumai, Reiji; Murakami, Youichi; Oshio, Hiroki (Royal Society of Chemistry, 2016)
A cyanide-bridged [Co3Fe2] cluster with trigonal bipyramidal geometry shows solvent-driven reversible on/off switching of its thermally induced electron-transfer-coupled spin transition (ETCST) behaviour.